Banks and sovereigns: an econometric analysis of an entangled relationship - Mendes, Ana Rita Semião (2015)
In this discussion OLS regressions are used to study the factors that influence sovereign yield spreads and domestic bank indeces for a set of euro area countries. The results show that common factors explain changes in bank indeces better than in the yields. Moreover, although there is some country differentiation, a common pattern among all is visible. A contemporary spillover effect between banks and sovereigns emerged after bank bailouts and became stronger with the burst of the sovereign debt crisis. The vicious cycle between the two has contributed to the escalation of spreads and to painful austerity measures.